Knowledge and awareness regarding eye donation among medical and para medical students in a tertiary care hospital in Odisha: a comparative study - Rattan, Ankit; Sahoo, Antaryami; Khan, Z. U.; Patnaik, Archana; Singh, Priyatama; Rath, Mahesh (International Journal Of Community Medicine And Public Health, 2019)
Background: India needs around 2,77,000 donations annually to perform 1,00,000 corneal transplants. To enhance the procurement of corneal donations further, raising the level of public education on eye donation was the most important first step. The Govt. of India under the 11th 5-year plan envisages eliminating avoidable blindness completely by 2020. The aim and objective of the study was to compare the awareness of eye donation and willingness to donate eyes among medical and paramedical students. Methods: A cross sectional study was carried out among 400 final year MBBS students and interns and also among the final year B.Sc. nursing students and at Hi-Tech Medical College and Hospital, Bhubaneswar from August 2018 to September 2018. Results: The study participants were in the age group of 18-25 years. While 100% medical students had heard about organ donation, 85.5% of paramedical students heard about organ donation. Positive opinion regarding donation of eye post death was got from all the medical students as against 85% of paramedical students. More than 1/3rd of the study participants in both the groups were willing to donate eyes and know more regarding the same and also had a fair idea regarding shortage of donors in India. Conclusions: Awareness of eye donation is better in medical students compared to paramedical students, preferably due to the exposure and study curriculum. Most of the students in both groups were inclined to pledge for eye donation. Awareness regarding eye donation will form the prime base for the elimination of avoidable blindness in India.